English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

Can someone please help me answer this?

Evaluate: a^3 + ab^2 - ab if a = -1/3 and b = -1/2

2007-04-29 16:26:52 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

a^3 + ab^2 - ab
if a = -1/3 and b = -1/2
therefore,
(-1/3)^3 + (-1/3)(-1/2)^2 - (-1/3)(-1/2)
= -1/27 + (-1/3)(1/4) - 1/6
= -1/27 - 1/12 - 1/6
= (-8 - 18 - 36)/216
= -62/216
= -31/108

2007-04-29 16:36:42 · answer #1 · answered by lkl916 1 · 0 0

a^3 + ab^2 - ab ; a = -1/3 and b = -1/2
(-1/3)^3 + (-1/3)(-1/2)^2 - (-1/3)(-1/2)
(-1/27) + (-1/3)(1/4) - (1/6)
(-1/27) - (1/12) - (1/6)
(-1/3)(1/9 + 1/4 + 1/2)
(-1/3) [(4+9+18)/36]
(-1/3) (31/36)
-31/108

2007-04-29 23:40:00 · answer #2 · answered by aquarian8502 2 · 0 0

a^3 + ab^2 - ab
= (-1/3)^3 + (-1/3)(-1/2)^2 - (-1/3)(-1/2)
= (-1/9) + (-1/3)(1/4) - (1/6)
= -1/9 - 1/12 - 1/6
= -4/36 - 3/36 - 6/36
= -13/36

2007-04-29 23:33:53 · answer #3 · answered by QiQi 3 · 0 2

-1/27 - 1/12 + 1/6

-4/108 - 9/108 + 18/108

5/108

2007-04-29 23:35:15 · answer #4 · answered by TychaBrahe 7 · 0 1

fedest.com, questions and answers